2012
DOI: 10.1093/carcin/bgs139
|View full text |Cite
|
Sign up to set email alerts
|

EGF promotes neuroendocrine-like differentiation of prostate cancer cells in the presence of LY294002 through increased ErbB2 expression independent of the phosphatidylinositol 3-kinase-AKT pathway

Abstract: An increased neuroendocrine (NE) cell population in prostate cancer is associated with more aggressive disease and recurrence after androgen-deprivation therapy, although the mechanism responsible is unknown. In this study, we report that the treatment of LNCaP cells with epidermal growth factor (EGF) in the presence of LY294002, an inhibitor of the phosphoinositol 3'-kinase (PI3K)-AKT pathway, induced an increase of levels and activity of ErbB2. Under these conditions, we also observed cell survival and NE di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…EGFR has been shown to signal through various pathways including the MAPK-pathway [40], and EGF treatment has been demonstrated to promote neuroendocrine-like state in LNCaP cells [41]. Taken together, this adds support to role of the MAPK pathway seen previously (Figure 6) in the NED process.…”
Section: Resultssupporting
confidence: 79%
“…EGFR has been shown to signal through various pathways including the MAPK-pathway [40], and EGF treatment has been demonstrated to promote neuroendocrine-like state in LNCaP cells [41]. Taken together, this adds support to role of the MAPK pathway seen previously (Figure 6) in the NED process.…”
Section: Resultssupporting
confidence: 79%
“…Transient TPD52 isoform knock‐down also produced increased cell death in LnCaP prostate cancer cells , and in the androgen‐independent derivative cell line C4‐2 . As both LnCaP and C4‐2 cells express ERBB2 the consequences of TPD52 knock‐down in these cell lines are consistent with TPD52 promoting the survival of ERBB2‐positive cancer cells. However, Kourtidis et al also reported that the ERBB2‐negative breast cancer cell line MDA‐MB‐468 showed similar reductions in viability to TPD52 knock‐down as ERBB2 ‐amplified and/or ‐expressing cell lines.…”
Section: Discussionmentioning
confidence: 65%
“…Alonzeau J et al. found 26RFa might participate in the development of PCa via promoting the PCa NE differentiation (Alonzeau et al., 2013), and IL‐6, EGF or Wnt‐11 could induce NE‐like differentiation in LNCaP cells (Qiu et al., 1998,Cortés et al., 2012).…”
Section: Discussionmentioning
confidence: 99%